Sistem Kendali PID pada Modus Transisi Terbang Tiltrotor - Syafrizal Akhzan; Andi Dharmawan (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
Tiltrotor is an unmanned aerial vehicle which can take off vertically and fly with full speed. These abilities are supported by actuators, which can change the angle of propellers in transition mode. Without control system in hovering mode and transition mode, it will be difficult to control tiltrotor. The purpose of this research is to design the system which can stabilize the tiltrotor by maintaining oriented angle of tiltrotor’s roll, pitch, and yaw in hovering mode and transition mode using PID controller.PID controller uses negative feedback which is obtained from accelerometer, gyroscope, and magnetometer by using DMP method and Madgwick quaternion to produce the pulse to control the velocity of brushless motor and angle position of servo motor. The result of PID controller is also compared to P controller and PI controller.According to the test, control system in transition mode for roll angle with setpoint 0o is capable to maintain roll angle at average angle 0.48o with standard deviation 1.75o, for pitch angle with setpoint 25o is capable to maintain pitch angle at average angle 25.26o with standard deviation 2.87o, for yaw angle is capable to maintain yaw angle at range 10o to 0o with average angle 3.78o and standard deviation 1.83o.